The Role of Libraries, Archives and Information Centres in the Formation of Critical Thinking and Civic Values in the Digital Society: Global, European and Ukrainian Strategies - N. Khymytsia; О. Morusko (Вісник Харківської державної академії культури)
The relevance of the article. Today’s digital society faces unprecedented challenges from the spread of disinformation, information warfare, and the rise of manipulative technologies. This undermines democratic values, weakens trust in institutions, and makes it difficult to build civic solidarity. In the context of information overload, libraries, archives, and information institutions are becoming particularly relevant as conductors of reliable information, the development of critical thinking, and civic values.